Higher Education Institutions (HEIs): pioneers of Sustainable Campuses / Dr. Farah Adilla Ab Rahman and Jeniwaty Mohd Jody - Ab Rahman, Farah Adilla; Mohd Jody, Jeniwaty (Academy of Language Studies, Universiti Teknologi MARA Negeri Sembilan Branch, Rembau Campus, 2024)
In an era where environmental consciousness is paramount, universities are taking significant strides to create campuses that not only foster academic excellence but also embody a commitment to sustainability. The imperative for universities to adopt green and sustainable practices is underscored by their pivotal role in shaping future leaders and opinion-makers committed to sustainability (Dabija, Câmpian, Tiron-Tudor, & Stanca, 2023). Hence, this article aims to explore the multifaceted efforts of HEIs in driving sustainability, focusing on key research findings illuminating the transformative journey towards Sustainable Campuses.